Mobilidade precária em Terra estrangeira e em Estive em Lisboa e lembrei de você - Marco Antonio Rodrigues (Estudos de Literatura Brasileira Contemporânea)
The article investigates the representation of the migration of lower middle-class Brazilians to Portugual in the movie Terra estrangeira (1995), by Walter Salles, and the novel Estive em Lisboa e lembrei de você (2009), by Luiz Rufatto, from topics such as mobility, identity, deterritorialization and rooting. With the reading of the works, we conclude that they exemplify that mobility is not the exclusive privilege of the elite, and when this mobility takes place in poor conditions, resulting in uprooting and identity precarious.